The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5530/pj.2020.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Macaranga gigantea Leaf Extracts: Production and Characterization

Abstract: Macaranga is a genus of the family Euphorbiaceae which comprises of about three hundred species. It is present in some parts of the world which include Indonesia, some parts of Africa, Madagascar, Asia, the east coast of Australia and the Pacific islands. 7-15 The Macaranga gigantea plants are known to be in the form of shrubs or trees and grow in places with optimum sunlight, secondary forests or forests that have been destroyed. Macaranga gigantea plants show several bioactivity which include antitumor, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…It is a rapid process that does not involve severe heat treatment; therefore, it is a suitable method to preserve biological products, including temperaturesensitive products, without their degradation; it also allows for storage at room temperature [31][32][33][34][35][36][37][38][39][40]. It is an instantaneous process where spherical and uniform samples can be obtained, and the process can be easily scaled up [30][31][32][33][34][35][40][41][42][43][44][45]. The effectiveness of the solvent evaporation method to produce microspheres depends on the successful entrapment of the active agent within the particles, and thus, this process is most successful with drugs which are either insoluble or poorly soluble in the aqueous medium, which comprises the continuous phase [32,39,[46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…It is a rapid process that does not involve severe heat treatment; therefore, it is a suitable method to preserve biological products, including temperaturesensitive products, without their degradation; it also allows for storage at room temperature [31][32][33][34][35][36][37][38][39][40]. It is an instantaneous process where spherical and uniform samples can be obtained, and the process can be easily scaled up [30][31][32][33][34][35][40][41][42][43][44][45]. The effectiveness of the solvent evaporation method to produce microspheres depends on the successful entrapment of the active agent within the particles, and thus, this process is most successful with drugs which are either insoluble or poorly soluble in the aqueous medium, which comprises the continuous phase [32,39,[46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl cellulose is a non-biodegradable hydrophobic polymer. [11][12][13][14][15] The microparticle hardening rate of these polymers is unknown. As a result, it's important to understand how polymer properties affect the hardening time of polymeric microparticles.…”
Section: Resultsmentioning
confidence: 99%
“…3 Polymers with various physical properties (such as solubility, molecular weight, reactivity, viscosity, biodegradability, permeability, and so on) have been applied to create microparticles. [11][12][13][14][15] In the emulsi cation phase of a heterogeneous polymerisation device, particle size and particle size distribution are important. [14][15][16][17] The laser light scattering method has been used extensively to measure certain parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was to use a solvent evaporation method to create microcapsules from Macaranga gigantea (M. gigantea) leaves extract utilizing ethocel 10 centi poise (cP) and Eudragit E100 as a matrix. It can be concluded that employing Eudragit E100 and ethocel 10 cP as a polymer matrix, microcapsules of M. gigantea leaves extract may be made by solvent evaporation [138].…”
Section: Microencapsulationmentioning
confidence: 99%